Blood Cell Count Biomarkers, Risk, and Outcomes of Ischemia-Related Lower Limb Amputations: A Systematic Review. (December 2022) - Dettori, Paola; Mangoni, Arduino Aleksander; Zinellu, Angelo; Carru, Ciriaco; Paliogiannis, Panagiotis
Lower limb amputations due to ischemia represent an important health care and social issue. However, there are currently no specific biomarkers able to predict the risk of amputation and postamputation complications and prognosis. We conducted a systematic review of studies investigating whether blood cell count indexes of systemic inflammation are linked to the risk and the outcome of lower limb amputations due to ischemia. Overall, in 22 studies involving 8832 patients selected for review, several blood cell count indexes, particularly the neutrophil lymphocyte ratio, showed some promise in terms of predicting amputations and general outcomes of conservative and surgical treatments, as well as postamputation complications and prognosis. However, largely due to methodological limitations, further prospective studies are required to establish the clinical utility and applicability of blood cell indexes in the routine management of patients with ischemia-related lower limb amputations.